A systematic study on the efficacy of low-temperature GaN regrown on p-GaN to suppress Mg out-diffusion - Lee, Kwang Jae; Wen, Xinyi; Nakazato, Yusuke; Chun, Jaeyi; Noshin, Maliha; Meng, Chuanzhe; Chowdhury, Srabanti (Frontiers in Materials, 2023)
Embedding p-GaN in AlxGa1-xN-based thin films has garnered significant interest as a versatile structure for bandgap engineering such as tunnel/super-junctions or current blocking/guiding functions in electronic devices. However, Mg, a p-GaN dopant, has an undesirable diffusive capacity into the nearby thin films at a high growth temperature (>1000 oC), resulting in structural challenges in device design. This study systematically investigated the low-temperature GaN (LT-GaN) layer regrown on p-GaN that suppresses Mg diffusion according to metal-organic chemical vapor deposition (MOCVD) growth conditions. Prototype Al0.3Ga0.7N (40 nm)/GaN (140 nm) high-electron-mobility transistors (HEMTs) were regrown with LT-GaN on p-GaN (300 nm), and a high two-dimensional electron gas (2DEG) density of 3.13E12 cm-2 was achieved by inserting a 100 nm-thick LT-GaN layer grown at 750 oC, in contrast with only 1.76E10 cm-2 2DEG density was obtained from Al0.3Ga0.7N/GaN HEMTs regrown directly on p-GaN (Mg: 4.0E19 cm-3). The fabricated Al0.3Ga0.7N/GaN HEMTs with 100 nm-thick LT-GaN demonstrated a high drain current density of 84.5 mA/mm with a low on-state resistance of 31 Ω·mm. The AlxGa1-xN/LT-GaN/p-GaN platform demonstrated here paves the way for various III-nitride-based structures with embedded p-GaN.